Bendamustine in lymphomas: a review of its use. Issue 2 (12th March 2012) - Cañamares, I.; Gomez-Baraza, C.; Agustin, M.J.; Llama, N. de la; Real, J.M.; Abad-Sazatornil, M.R.
Abstract : Background: Bendamustine is an alkylating agent recently approved in several European countries for non-Hodgkin's lymphoma (NHL) refractory to rituximab (R). Purpose: To describe bendamustine use in lymphomas and review safety in our clinical practice. Materials and methods: Retrospective study carried out during 2010. The following data were collected: sex, age, previous treatment, bendamustine dosage, treatment duration, % adverse reactions (ARs), % colony-stimulating factor required and reduction of the initial dose of bendamustine. Results: 7 patients received bendamustine: 71.4% male, age 53.9 at the beginning of bendamustine treatment. 42.8% Hodgkin's lymphoma (HL) and 57.2% NHL, 50.0% were mucosa-associated lymphoma tissue (MALT) and 50.0% follicular NHL. An average of 3 treatment lines were used before bendamustine was used. In NHL patients (n=4), first-line treatment was CHOP±R; several schemes were used in the second line (BEACOPP-14, DHAP). Bendamustine was used as third line: 50% combined with rituximab and 50.0% in monotherapy. There were no standard dose criteria for bendamustine: 90 mg/m2 (2 patients), 100 mg/m2 and 120 mg/m2 one each. In HL patients (n=3), 2 patients received ABVD followed by bone marrow transplant and 1 patient BEACOPP-14 at first. In second and third-line treatment different schemes were administered (BEACOPP-14, GEMOX, DHAP and CNOP). As the fourth line bendamustine was requested as off-label at 110-120 mg/m2. In this study, bendamustine treatment was continued for 22.85 weeks (95% CI 19.11 to 26.60). The most common AR was haematological toxicity (85.7%); grade 3-4 neutropenia appeared in 9.5% and anaemia in 4.8% of patients. Use of colony-stimulating factor and epoetin alfa were essential in 71.4% patients; it was not necessary to reduce the dose of bendamustine. Other ARs were fatigue 14.3%, fever, nausea or vomiting 9.5%. Conclusions: Experience with bendamustine in Hodgkin's and Non-Hodgkin's lymphoma in our institution is limited. Haematological toxicity is common and can be managed with colony-stimulating factor.